결혼이민자 가정 유아의 유아교육기관 생활 경험에 대한 질적 연구 - 박미경(Mi Kyung Park); 엄정애(Jung Ae Ohm) (Korean Journal of child studies, 2007)
In South Korea, some interethnic families result from prearranged marriages where 1 spouse is an immigrant. In this study, traits of children in families of interethnic immigrant marriages were studied by individual interviews of ten kindergarten teachers responsible for them and 8 observations of their preschool classes. Subjects were 21(13 male, 8 female) 3- to 5-year-old children. Results showed the diverse traits of these children : they adapted to the environment by changing and getting along, but some of them exhibited problematic behavior such as delayed language development, confused identity, and aggression. The attitude of their peers included passive reaction, discord and receptivity regarding their difference. The attitude of the teachers was a sense of responsibility and worry.